Studi Eksperimental Pengukuran Medan Listrik pada Isolator Transmisi 275 kV PT. INALUM Menggunakan Positron Insulator Tester - Joya Margaretha Siregar; Hisar Alexcandra; Arwadi Sinuraya; Desman Jonto Sinaga (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to determine the characteristics and distribution of electric fields in the 275 kV transmission line insulator owned by PT. Indonesia Asahan Aluminum (INALUM) uses a Positron Insulator Tester. The background of this research departs from the importance of insulator maintenance as a vital component in maintaining the reliability of the extra-high voltage transmission system (SUTET). The method used is experimental by taking direct measurements on several randomly selected transmission towers in the field without shutting down the system. The measurement data is analyzed to determine the magnitude of the electric field and detect anomalies in the voltage distribution in each insulator piece. The measurement results showed that the highest electric field value was in the insulator chip closest to the voltage conductor, while the lowest value was found in the chip close to the tower structure. The non-linear distribution pattern of the electric field indicates a potential decline in insulator quality. The results of this study prove that the use of the Positron Insulator Tester is effective in detecting insulator conditions quickly and safely, so that it can be a reference in the preventive maintenance program of high-voltage transmission networks.